2020
DOI: 10.1016/j.gloepi.2020.100033
|View full text |Cite
|
Sign up to set email alerts
|

Should air pollution health effects assumptions be tested? Fine particulate matter and COVID-19 mortality as an example

Abstract: In the first half of 2020, much excitement in news media and some peer reviewed scientific articles was generated by the discovery that fine particulate matter (PM2.5) concentrations and COVID-19 mortality rates are statistically significantly positively associated in some regression models. This article points out that they are non-significantly negatively associated in other regression models, once omitted confounders (such as latitude and longitude) are included. More importantly, positive regression coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Indeed, the lack of available data of COVID‐19 cases for the initial outbreak weeks in China hampered the assessment of air pollution effects before governmental actions were undertaken (Xu et al., 2020 ). Thus, our results contrasted with those of other studies showing particulate matter and pollutant gases (CO, NO 2 , and O 3 ) as being positively associated with the number of cases and mortality from COVID‐19 in China (Cox & Popken, 2020 ; Zhu et al., 2020 ). Hence, our result should be interpreted carefully, considering the effects of how each country managed the disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, the lack of available data of COVID‐19 cases for the initial outbreak weeks in China hampered the assessment of air pollution effects before governmental actions were undertaken (Xu et al., 2020 ). Thus, our results contrasted with those of other studies showing particulate matter and pollutant gases (CO, NO 2 , and O 3 ) as being positively associated with the number of cases and mortality from COVID‐19 in China (Cox & Popken, 2020 ; Zhu et al., 2020 ). Hence, our result should be interpreted carefully, considering the effects of how each country managed the disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Last but not least, regression models (as used in this paper) in epidemiological research that involves air pollution are not perfect tools for assessing whether reducing exposure to air pollution will reduce the risk of harm to human [ 27 ]. This role is assigned for the traditional scientific method based on the testing predictive generalizations against data.…”
Section: Discussionmentioning
confidence: 99%
“…This role is assigned for the traditional scientific method based on the testing predictive generalizations against data. It is worthy to underline that science should be completed (not substituted) by regression models [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have found that air pollution has impact on COVID-19 associated mortality. [27][28][29] This study found a link between the AQI of 77 territories and total COVID-19 cases, but high AQI is not always a predictor for COVID-19 incidence. There are numerous variables that may contribute to SARS-CoV-2 transmission, including strictness of preventive measures, border control, 30 implementation of social distancing, and individual expression of the angiotensin converting enzyme 2 (ACE2) receptor, for which increased expression has been associated with increased risk of COVID-19.…”
Section: Discussionmentioning
confidence: 58%